One-Stop Shopping Platform: Transformasi Katalog Elektronik dalam Pengadaan di Sektor Kesehatan - Ridwan Ridwan; Ferdianto Dwiputra; Gayuh Ardhi Rumpoko; Muhammad Iqbal Mutaqin (Pajak dan Manajemen Keuangan, 2025)
Electronic Catalog Version 6 marks a significant advancement in Indonesia's government procurement system through comprehensive feature enhancements. This updated platform introduces key innovations, including a centralized product category management system that ensures standardization across all procurement processes. The system features enhanced notification capabilities, streamlined order management, and a transparent payment integration framework that facilitates seamless transactions. A notable addition is the integrated spending monitoring dashboard, which enables real-time tracking of procurement activities and supports efficient product management. The platform's successful implementation hinges on thorough stakeholder preparation and systematic user training programs. These improvements are specifically designed to optimize procurement efficiency and elevate public service quality, with a particular focus on strengthening the healthcare sector's procurement processes.